#TAIA2012 - Diaz, Fernando; Dumais, Susan; Radinsky, Kira; Rijke, Maarten de; Shokouhi, Milad (ACM SIGIR Forum, 2012)
The SIGIR 2012 Workshop on Time-aware Information Access (#TAIA2012)1 was held in Portland on Thursday, 16 August 2012. The workshop brought together about 50 researchers from academia and industry for a full-day programme on time-sensitive information access that involved three keynotes and nine paper presentations.